An Assessment of the Curriculum of Islamic Banking and Finance Degree Programme Incorporating Employers’ Expectation - Abi Huraira Rifas; Raseethu Mohamed Kasjin (Department of Sharia Financial Management, Institut Agama Islam Negeri Sultan Amai Gorontalo, Indonesia, 2024)
Scholars and experts are produced by any institutions in which a better curriculum is taught. Education acquired through a good syllabus is disseminated in various fields. Nowadays, Islamic Banking and Finance industry has become a burning professional concept since its institutionalization in 1960’s. As this study focusses on the curriculum, the main objective of this study is to assess the curriculum of Bachelor of Arts honors in Islamic Banking and Finance degree which is how far incorporated the expectation of the employers. This study has been designed based on qualitative research method. Documentary review technique was employed for the study. Students’ hand book, students’ guide, university website, other service providing divisions, journal articles, books and faculty board minutes have been utilized for data collection and has used documentary analysis technique for analyzing and discussion. In addition, data collected via the questionnaire with open questions from 52 graduates. MS Excel 2016 version has also been used for the interpretation using tables. The findings reveal that the curriculum over-all has incorporated the required career qualification skills at most. It needs a little revision to be effective, though all kinds of resources and facilities are provided by the SEUSL during the period. It provides what elements are to be considered while the curriculum is formed. According to the suggestions, the department might consider the significant revisions at the next major curriculum revision. The researchers underline that every curriculum of any studies should be revised based on the present context to clear the barrier of making decision in future.